Magnetic and microwave absorption properties of PVB/Fe3O4 and PVB/NiFe2O4 composites - AKIN, EMRE; ÇAKIR, MUSTAFA (WILEY, 2018)
Electromagnetic and microwave absorbing properties of Polyvinylbutyral (PVB)/Fe3O4 and PVB/NiFe2O4 composites were investigated in the 1-14 GHz. PVB/filler particles (Fe3O4 and NiFe2O4) composites were prepared with 90/10 mixture ratios via Ultrasonic Probe Sonicator method in solution. The complex permittivity (epsilon-j epsilon) and permeability (- j) of the composites have been measured at different microwave frequencies in 1-14 GHz employing vector network analyzer (Keysight N9926A). The reflection loss (R-L) of composites was calculated and evaluated using theory of the absorbing wall. It was found that, both composites exhibit the large reflection loss and broadband within the frequency range from 1 to 14 GHz for 3, 5, and 7 mm. However, the R-L results show that, when the thickness is 7 mm, the minimum R-L was found to be -22.9 dB (99% power absorption) at the frequency of 13.93 GHz. The Fe3O4/PVB and NiFe2O4/PVB composites have potential application for microwave and radar absorptions. POLYM. COMPOS., 39:3418-3423, 2018. (c) 2017 Society of Plastics Engineers
Keywords: RADAR ABSORBING MATERIALS; CARBONYL IRON; FERRITE; FREQUENCY; DESIGN